Pemanfaatan pekarangan dalam upaya mendukung ketahanan pangan keluarga - Sunanti, Titis; Aviory, Koryna (University of Islam Malang, 2021)
The food security of households is the ability of a family to meet family food needs independently. The food security of households can be strengthened by making use of home yards. This service is an activity that involves the community in strengthening the food security of households. This service consists of several activities, such as (1) promoting planting activities so that residents become motivated; (2) provide counseling on family food security and its strategies, and (3) provide training on horticultural cultivation. This activity was carried out well. The number of residents doing planting activities has increased by 75.38%. While the results of the citizen questionnaire related to this service activity showed a good response with a percentage of 77.6%. The residents hope that the community service activities can be continued with other types of activities, such as assistance to develop existing activities in the nursery.